Sunny figures it out - Holm, Jennifer L. (Holm, Jennifer L. Sunny, 2025)
"...SUNNY series continues with Sunny trying to figure out when a boy stops being just a friend and starts being a boyfriend... and what that means for both of them. There's no question that Sunny has fun whenever she hangs out with Tony. They go to the movies together, talk a lot at school, and support each other when they need it. But are they dating? Sunny isn't sure... but her friend, Deb, is. She thinks Sunny and Tony should be doing the couples-skate at the local roller rink. And Tony should be giving Sunny his jacket to wear. And carrying her books to class. For Sunny, this doesn't feel great. It just feels... weird. Maybe she needs to stop taking everyone else's advice in order to figure things out for herself!"--Amazon.com.